Development of lift the flap book as memet (mathematics learning media) trigonometry materials for high school students - Nia Kurniaty Rukman; Ryan Nizar Zulfikar; Aida Puji Rahayu (Institute of Computer Science (IOCS), 2023)
This study intends to examine the viability, practicability, and efficacy of the lift-the-flap book as a trigonometry learning tool for high school students. This study uses the ADDIE approach for research and development (R&D). In this study, the population consisted of X grade students from SMA Negeri 1 Kupang, and the sample consisted of 31 XC grade kids. Data collection approaches employing questionnaires and assessments. Analyses of data's validity, applicability, and efficacy are data analysis methodologies. The findings of research on mathematics learning media lift-the-flap books for high school trigonometric comparative materials. The findings of material expert testing were 91.7% with a very good category, while the results of media expert testing were 94.6% with a very valid category. Based on the findings of the teacher's reaction with an average percentage value of 92% in the very good category and the average student response of 87.74%, the media is deemed practical. After passing the learning outcome test with an average score of 87.1% based on extremely good criteria, the media is utilized effectively in the learning process. Therefore, it can be concluded that the produced lift-the-flap book learning media can be applied to the study of mathematics trigonometric comparison material.